Pretrial Detention in the Time of COVID-19 - Carroll, Jenny E. (2020)
COVID-19 has shone a light on the preexisting flaws in the criminal justice system. This Essay focuses on one of the challenges the criminal justice system faces in light of COVID-19: that of a pretrial detention system that falls more harshly on poor and minority defendants, swells local jail populations, is fraught with bias, produces unnecessarily high rates of detention, and carries a myriad of downstream consequences, both for the accused and the community at large. Long before the first confirmed case, United States' jails were particularly susceptible to contagions. The COVID-19 crisis exacerbates this problem creating an acute threat to the health of those in custody and those who staff our jails. The pandemic reveals that even during ordinary times the pretrial detention system fundamentally miscalculates public safety interests to the detriment of both detainees and the communities they leave behind. Simply put, current pretrial detention models fail to account for the risks defendants face while incarcerated and pit defendants' interests against the very communities that depend on them